From creation of the universe to a whale rider: exploring traditional tales in the digital promotion of New Zealand / Norhanim Abdul Razak - Abdul Razak, Norhanim (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The paper applied a content analysis method to examine how myths and legends have been employed by the promotional organization in portraying New Zealand on the official tourism website. The assessment of the website uncovered six main legends which have been presented in the promotion of New Zealand to potential tourists. These traditional tales have been incorporated into the website chiefly as part of Maori heritage attributes in which purakau (the Maori term for legends) represents among crucial aspects in understanding their worldviews and cultural identities. Legends narrating fishing voyages involving demi gods offers a mythological explanation of the origin of the geological formation of islands of New Zealand were presented more than once on the website. Among legends presented to readers on the websites encompass stories of Tane Mahuta, which depicts the tale of the sky father, the earth mother, and the creation of the world of light that humans live in today. Another unique legend, Paikea the whale rider, is featured as part of the description of a whale-watching attraction in Kaikoura, Christchurch. The overall analysis uncovered that legendary tales are incorporated into the website as the part historical origin of Maori people and in the promotion of several tourist attractions in New Zealand. From a tourism perspective, the representation of these tales enhances the appeal of destinations and making them more outstanding to visitors. The inclusion of the purakau offers tourists a deeper understanding of the cultural heritage of this country. Furthermore, Maori worldviews on the creation of the universe and formation of the natural environment are transpired. It is noticeable through these legends that Maori people strongly respect their ancestors and highly appreciated natural resources. Finally, the emphasis on environmental conservation and sustainability as ingrained in the tales further supported the overall promotional tagline of 100% Pure New Zealand and the inclusion of Tiaki Promise on the official tourism website.